Nucleolar Sequestration: Remodeling Nucleoli Into Amyloid Bodies - Wang, Miling; Bokros, Michael; Theodoridis, Phaedra Rebecca; Lee, Stephen (Frontiers in Genetics, 2019)
This year marks the 20th anniversary of the discovery that the nucleolus can temporarily immobilize proteins, a process known as nucleolar sequestration. This review reflects on the progress made to understand the physiological roles of nucleolar sequestration and the mechanisms involved in the immobilization of proteins. We discuss how protein immobilization can occur through a clever and highly choreographed amyloidogenic program that converts the nucleolus into a large fibrous organelle with amyloid-like characteristics called the Amyloid body (A-body). We propose a working model of A-body biogenesis that includes a role for low complexity ribosomal intergenic spacer RNA (rIGSRNA) and a discrete peptide sequence, the amyloid-converting motif (ACM), found in many proteins that undergo immobilization. Amyloid-bodies provide a unique model to study the multi-step assembly of a membrane-less compartment and may provide alternative insights into pathological amyloidogenesis involved in neurological disorders.